Digitalization of the tardigrade collection of Giuseppe Ramazzotti - Silvia Zaupa; Diego Fontaneto; Roberta Piscia; Lyudmila Kamburska (Journal of Limnology)
The Collection of Tardigrada by Giuseppe Ramazzotti, preserved at the Water Research Institute of the National Research Council (CNR-IRSA) in Verbania, Italy, is composed of numerous slides and microscopic preparations of tardigrades, including animals and their eggs. It is a historical collection that includes samples taken over a period of years from 1938 to 1964 in Europe, Africa, North and South America by one of the Italian taxonomists working on the phylum Tardigrada. The dataset of the Ramazzotti Collection is composed of 3319 records, prepared within the Project ITINERIS (ITalian INtegrated Environmental Research Infrastructures System) dedicated to build the Italian Hub of Research Infrastructures in the environmental scientific domain. The purpose of creating this dataset is to protect the information through the digitalization of the samples, and to facilitate sharing the information on the animals collected by Ramazzotti and stored at CNR-IRSA, Verbania Pallanza. For this reason, each record in the database is associated with a photograph of the microscopic slide and with a photograph of the animal. The data is organized into a standardized Darwin Core Archive format, thus available globally, through the Global Biodiversity Information Facility infrastructure (GBIF). The Collection is also registered in the Global Registry of Scientific Collections (GRSciColl).